2017
DOI: 10.1002/2017jc012887
|View full text |Cite
|
Sign up to set email alerts
|

Fingerprints of Sea Level Rise on Changing Tides in the Chesapeake and Delaware Bays

Abstract: Secular tidal trends are present in many tide gauge records, but their causes are often unclear. This study examines trends in tides over the last century in the Chesapeake and Delaware Bays. Statistical models show negative M2 amplitude trends at the mouths of both bays, while some upstream locations have insignificant or positive trends. To determine whether sea level rise is responsible for these trends, we include a term for mean sea level in the statistical models and compare the results with predictions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
67
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 56 publications
(70 citation statements)
references
References 97 publications
(172 reference statements)
3
67
0
Order By: Relevance
“…Changes in water depth due to geocentric (or absolute) MSL rise or geological processes such as the crust's glacial isostatic adjustment (GIA) have been explored as one of the main drivers of changes in tide at the regional/global scale (Arns et al, ; Flather et al, ; Greenberg et al, ; Kemp et al, ; Müller et al, ; Pickering et al, ; Ross et al, ; Schindelegger et al, ). Tides behave as shallow‐water waves and thus are strongly affected by water depth.…”
Section: Potential Mechanisms Causing Changesmentioning
confidence: 99%
See 3 more Smart Citations
“…Changes in water depth due to geocentric (or absolute) MSL rise or geological processes such as the crust's glacial isostatic adjustment (GIA) have been explored as one of the main drivers of changes in tide at the regional/global scale (Arns et al, ; Flather et al, ; Greenberg et al, ; Kemp et al, ; Müller et al, ; Pickering et al, ; Ross et al, ; Schindelegger et al, ). Tides behave as shallow‐water waves and thus are strongly affected by water depth.…”
Section: Potential Mechanisms Causing Changesmentioning
confidence: 99%
“…With water depths adjusted for GIA and geocentric MSL changes, the model could reproduce the sign of the observed M 2 amplitude trends at 36 out of 45 analyzed tide gauge stations in Europe and Australia (Figure ), and at the North Atlantic American coasts (Figure ). Schindelegger et al () additionally reported success in capturing large fractions (order 50% or more) of the magnitude in measured M 2 changes, primarily in shallow seas dominated by frictional effects, for example, the Gulf of Mexico, the German Bight, the Northwest Australian Shelf, and the Chesapeake‐Delaware Bay system; see also Ross et al () for a comparison of tide gauge data with modeling results in the latter area. Yet changes in water depth alone appear inadequate to explain some of the very large trends seen in tidal amplitude on the European Shelf (e.g., the English Channel and the Irish Sea) as well as the Gulf of Maine.…”
Section: Potential Mechanisms Causing Changesmentioning
confidence: 99%
See 2 more Smart Citations
“…Despite these similarities in freshwater forcing, the patterns of circulation and stratification in the two estuaries differ considerably. Tidal amplitude is greater in DB, in part due to differences in shape of the two bays, funnel for DB and dendritic for CB (Ross et al, ). Stronger tides in DB and a deeper central channel in CB (Figure a) lead to DB being relatively well mixed (Sharp et al, ) and CB being partially stratified (Schubel & Pritchard, ).…”
Section: Study Regionsmentioning
confidence: 99%